2022
DOI: 10.1097/hjh.0000000000003074
|View full text |Cite
|
Sign up to set email alerts
|

Initial combination therapy for hypertension in patients of African ancestry: a systematic review and meta-analysis

Abstract: We systematically reviewed randomized controlled trials (RCTs) that consider the effect of initial dual antihypertensive combination treatment on blood pressure (BP), morbidity, or mortality in hypertensive African ancestry adults, using the methodology of the Cochrane Collaboration. Main outcomes were difference in means (continuous data) and risk ratio (dichotomous data).We retrieved 1728 reports yielding 13 RCTs of 4 weeks to 3 years duration (median 8 weeks) in 3843 patients. Systolic BP was significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
(361 reference statements)
0
6
0
Order By: Relevance
“…BP associations with CV risk have also been broadly consistent across ethnic groupings [1051]. Based on systematic reviews [1052] in people of SSA ancestry, CCB and diuretic monotherapies appear to be more effective than BB and ACEi monotherapies, with combination therapy between major drug classes allowing a substantial group of patients (50-70%) to reach BP control [1052,1053]. This is similar to the results of the ALLHAT trial in the USA, which included 33% African Americans [566,1054] and found that BP control at 4 years was 63, 60 and 54% with chlorthalidone, amlodipine, and lisinopril-based therapy, respectively.…”
Section: Managementmentioning
confidence: 88%
See 1 more Smart Citation
“…BP associations with CV risk have also been broadly consistent across ethnic groupings [1051]. Based on systematic reviews [1052] in people of SSA ancestry, CCB and diuretic monotherapies appear to be more effective than BB and ACEi monotherapies, with combination therapy between major drug classes allowing a substantial group of patients (50-70%) to reach BP control [1052,1053]. This is similar to the results of the ALLHAT trial in the USA, which included 33% African Americans [566,1054] and found that BP control at 4 years was 63, 60 and 54% with chlorthalidone, amlodipine, and lisinopril-based therapy, respectively.…”
Section: Managementmentioning
confidence: 88%
“…However, 24, 28 and 41% of patients of the corresponding groups received 3 drugs, including the BB atenolol. A recent systematic review and meta-analysis [1052] indicated that, in hypertensive adults of African ancestry, BP reduction was similar across initially administered dual combination therapy containing an RAS inhibitor with a CCB, or a diuretic while with a BB in combination therapy, SBP showed a 3.8 mmHg higher SBP compared with other combinations [1048,1052]. An RCT with African patients from seven SSA countries has also shown an effective BP reduction (ABPM) using a CCB in combination with either a Thiazide or an ACEi [1055].…”
Section: Managementmentioning
confidence: 99%
“…16,26,[68][69][70][71][72] Sex-neutral clinical practice guidelines [1][2][3] insufficiently acknowledge that clinical studies are often underpowered for women, such that "evidence creating" results could only be obtained for men or for both sexes together. Data particularly lack for specific subgroups, for example, pregnant women, women with gynecological disorders, women with a history of adverse pregnancy outcomes, women of color, and peri and postmenopausal women 16,26,[69][70][71] In addition, the higher cardiovascular risk with gynecological conditions and adverse pregnancy outcomes is absent from recommendations for history taking or currently used risk assessment tools, which tend to underestimate cardiovascular risk in women. [1][2][3]16,23,68 Moreover, women, especially women of color, less often receive the current, sex-neutral cardiovascular guideline-recommended care.…”
Section: Management Of Hypertension In Women Clinical Practice Guidel...mentioning
confidence: 99%
“…71 Metformin and RAS blockers have also been proposed for women with fibroids or a history of adverse pregnancy outcomes. 16,70,78 However, RAS blocker monotherapy might be less effective in women of African ancestry, 69 and these drugs are fetotoxic. [1][2][3] Finally, women tend to experience more adverse effects of antihypertensive drugs, probably due to understudied sex differences in pharmacokinetic or pharmacodynamic properties.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation